The role of information provision as a policy instrument to supplement environmental taxes: Empowering consumers to choose optimally - Eftichios S. Sartzetakis; Anastasios Xepapadeas; Emmanuel Petrakis (Fondazione Eni Enrico Mattei (FEEM), 2009)
The present paper examines, within a dynamic framework, the use of information provision as a policy instrument to supplement environmental taxation. We assume that at least a fraction of consumers do not posses the required information to make the optimal choices, and that their behavior at each time period depends on the accumulated stock of information. We show that, as the accumulated stock of information provision increases, both the optimal level of information provided at each period of time and the optimal tax rate decline over time. Our results provide strong evidence in support of information campaigns as a policy instrument to supplement traditional environmental policies. Information provision can shift the demand towards environmentally friendly products over time and thus, reduce the required level of the tax rate.
Keywords: Q53; Q58; D62; D82; 330; Information Provision; Environmental Taxation